Rediscovery of Sicydium nereoi (Cucurbitaceae), a critically endangered micro-endemic of riverine islands in Esquina, northeastern Argentina, with details on morphology, ecology, and conservation - Florentín, Javier E.; Medina, Walter A.; Delvescovo, Nadia S.; Pozner, Raúl (Phytotaxa, 2025)
This study provides a comprehensive morphological description and updated information of Sicydium nereoi, a microendemic climbing species of Cucurbitaceae, rediscovered in the riparian islands of Esquina, Corrientes, Argentina, after 50 years of being known only from the type specimen. We document for the first time the morphology of the pistillate flowers, fruits, and seeds, which differ from other Sicydium species by their ovoid, fleshy fruits, densely pubescent ovary, and glandular trichomes. A total of thirty-four individuals were recorded in three populations, restricted to an area of occupancy of 8 km² on organic-rich, calcareous soils. Based on IUCN criteria, we assign S. nereoi to the Critically Endangered (CR) category due to its limited distribution, small population size, and threats from habitat degradation and land use change. These findings provide key insights into the species’ morphological distinctiveness, ecological niche, and urgent conservation needs.